Antioxidant Activity and Consumer Preference of Brown Algae Sargassum hystrix Juice as a Functional Drink - Punky Kusuma Damayanti; Amir Husni; Siti Ari Budhiyanti (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2021)
Sargassum hystrix juice is a functional beverage made from S. hystrix through the immersion process, crushing, filtering, and pasteurization. Therefore, this study aims to determine the effect of S. hystrix concentration on antioxidant activity, level of consumer acceptance, and chemical composition of the juice. The fresh S. hystrix used were washed, immersed for three days, and blended at a concentration of 10, 20, 30, 40, and 50%, respectively. Meanwhile, the qualities of juice that were observed include yield, antioxidant activity, total phenol, water, ash, protein, and fiber content, formol number, total sugar, total plate count, and sensory analysis. The results showed that the S. hystrix juice had a value of yield 43.00-85.67%, pH 7.5, antioxidant activity 20.50-44.57%, total phenolic 32.78-293.11 mg GAE/g, water 93.03-95.39%, ash 0.36-6.34%, protein 0.88-4.96%, crude fiber 0.41-5.04%, formol number 15-21.67 mL N NaOH/100 mL, total sugar 3.10-4.61%, total plate count 2.3x103-4.3x103CFU/mL, sensory of color 1.83-2.95, flavor 2.49-3.29, and taste 2.29-3.50.